STRATEGI KOMUNIKASI PEMASARAN MATAYA ART AND HERITAGE PADA EVENT “PAMERAN KAIN NUSANTARA’’ - AJI, DEKY SETO (JURNAL KOMUNITAS, 2021)
This research is a case study because this research uses a qualitative approach and involves case study research. The result of this research is descriptive analysis. Sources of data in this study are words and actions obtained frominformants connected to research, while documents or other written sources areadditional data. The data analysis technique used interactive analysis. Analysis was carried out on all data obtained from interviews and documentation. The results ofthe research include History of the establishment of Mataya Arts AndHeritage, Organizational Structure of Mataya Arts And Heritage, Management ofMataya Arts And Heritage, Vision and Mission of Mataya Arts And Heritage, Cultural Event Activities " Cerita Kain tentang Kain " / Kain Nusantara Surakarta Held by Mataya Arts And Heritage, Marketing Communication Strategy with the "Friendship" Principle, Communication strategy to increase customer trust, Strategyfor selecting promotional media in the Mataya Arts And HeritageEventOrganizer. The conclusion of this research is the marketing communication strategy carried out by Mataya Art And Heritage at theKain Nusantara Event inSurakarta, and the social media used "Mataya Art And Heritage" and the researcher's expected that it can be used as input for the Event Organizer "Mataya Art And Heritage" inorder to they can be a successful Event Organizer and their services are always used by the company in doing promotions.